Performance of HIV detection in Zhejiang province in China: The Pareto principle at work. Issue 6 (4th May 2021) - Zhang, Jiafeng; Ding, Xiaobei; Zhou, Xin; Chen, Wanjun; Yao, Jiaming; Guo, Zhihong; Chen, Lin; Xia, Yan; Fan, Qin
Abstract: Background: Timely detection of HIV infection is critical for curbing the AIDS epidemic, and building an extensive and effective HIV laboratory network is of great importance. Therefore, improving quality management of the laboratory network and optimizing detection strategies are desirable research issues. Methods: We assessed the applicability of the Pareto principle to HIV detection performance. We conducted a retrospective review of basic information and numbers of screening tests among an HIV laboratory network (1, 452 laboratories) in Zhejiang province in 2014 and statistically analyzed HIV testing data for different population categories. Results: Approximately, 80% of the cumulative HIV screening tests and positive screening tests originated from 17.3% (251/1, 452) and 11.7% (170/1, 452) of the laboratories in the whole province, respectively, and similar patterns were observed at the prefectural level. We found that the top five population screening categories (25%, 5/20) had the highest contribution (approximately 80%) to not only the number of screening tests (77.2%) but also the numbers of positive (76.4%) and confirmed positive tests (81.5%). Conclusions: The Pareto principle provides a method for identifying noteworthy laboratories to deliver prior quality supervision and developing highly efficient screening strategies that best suit local needs. Abstract : Timely detection of HIV infection is critical for curbing the AIDS epidemic, and building an extensive and effective HIV laboratory network is of great importance. Therefore, improving quality management of the laboratory network and optimizing detection strategies are desirable research issues. We assessed the applicability of the Pareto principle to HIV detection performance. We conducted a retrospective review of basic information and numbers of screening tests among an HIV laboratory network (1, 452 laboratories) in Zhejiang province in 2014 and statistically analyzed HIV testing data for different population categories. Approximately, 80% of the cumulative HIV screening tests and positive screening tests originated from 17.3% (251/1, 452) and 11.7% (170/1, 452) of the laboratories in the whole province, respectively, and similar patterns were observed at the prefectural level. We found that the top five population screening categories (25%, 5/20) had the highest contribution (approximately 80%) to not only the number of screening tests (77.2%) but also the numbers of positive (76.4%) and confirmed positive tests (81.5%). The Pareto principle provides a method for identifying noteworthy laboratories to deliver prior quality supervision and developing highly efficient screening strategies that best suit local needs.